Ismail al-Faruqi’s Tawhidic Approach in the Context of IOK - Tasnim Abdul Rahman; Ahmad Nabil Amir (Universitas Hamzanwadi, 2023)
This study analyzed Ismail Raji al-Faruqi’s (1921-1986) fundamental ideas of education from the perspective of IOK and tawhidic framework and his critical contribution in articulating modern Islamic worldview and expounding its progressive and inclusive outlook. It set forth to discusses the ideas of Islamization of knowledge as envisaged and propounded in his major works that highlight the doctrine of tawhid and its overarching principle such as Islamization of Knowledge: General Principles and Work Plan, Al-Tawhid: Its Implications for Thought and Life dan etc. The study is based on library research using qualitative approaches by documenting sources derived from some major works of al-Faruqi and other relevant materials. The data was analyzed using descriptive, analytical, and comparative method. The study found that al-Faruqi has bring forth universal Islamic worldview that propounded transcendental religious and philosophical outlook based on his rational and universal premises. His philosophical ideal was founded on critical methodology of tawhid that was instrumental in projecting his Islamization of knowledge movement and in propounding its scientific and rational outlook in order to revived the spirit of reform and reconstructing ijtihad and reclaiming the universal and creative ummatic world order.